INVESTASI DAN TRADING DIPILIH UNTUK SAHAM PGAS - Aprilia Lukita, Safira; Ully Prisandini; Nerissa Arcellya Virjannah; I Made Suparta (Jurnal Nirta : Inovasi Multidisiplin, 2025)
Choosing a strategy between long-term investment and short-term trading is often an important decision for investors. This study explores both approaches on the stock of PT Perusahaan Gas Negara Tbk (PGAS), which is one of the energy sector stocks on the Indonesia Stock Exchange (IDX). In this journal, we analyze the performance of PGAS stock, examine the factors that influence its movement, and evaluate the potential returns and risks of both investment and trading strategies. The analysis shows that the investment and trading approaches to PGAS stock have their own advantages and disadvantages that investors need to consider according to their risk profile and investment objectives. Keywords: Investment, Trading, PGAS, Indonesia Stock Exchange, Investment Strategy, Stock Analysis